Co-adsorbing effect of bile acids containing bulky amide groups at 3β-position on the photovoltaic performance in dye-sensitized solar cells. (1st September 2019) - Soto-Navarro, Andrea; Alfaro, Ariel; Soto-Tellini, Víctor Hugo; Moehl, Thomas; Barea, Eva M.; Fabregat-Santiago, Francisco; Pineda, Leslie W.
Highlights: Novel co-adsorbates of bile acids with bulky group at 3β-position enhanced efficiency in DSSC with N719 ruthenium dye. Co-adsorbates#2 and#3 surpass efficiencies of assembled devices with deoxycholic acid. Photocurrent values (Jsc ) are enhanced owing to the minimization of aggregation. Diminishing of recombination is accomplished mostly for all devices compared to blank and CDOA. Abstract: Co-adsorbing molecules attain certain control in the surrounding of the dyes leading to enhanced efficiencies mainly by affecting the recombination of the photogenerated electrons and aggregation of dyes. Bile acids such as deoxycholic acid (DOA) and chenodeoxycholic acid (CDOA) yield competitive photovoltaic parameters. We harness the steroid backbone of bile acids to chemically modified it at its R3 position attaching sterically demanding amide groups rather than typically terminal hydroxyl groups (3β-position) as in DOA and CDOA. All possible resultant effects on the performance in complete DSSCs were studied by current density-voltage curves (e.g., percentage of efficiency, %η; open-circuit voltage, Voc ; short-circuit photocurrent, Jsc ; and fill factor, FF), incident photon-to-current conversion efficiency (IPCE), and a set of interfacial data by electrochemical impedance spectroscopy (EIS). Our co-adsorbates stand out by enhancing the conversion efficiencies, being in some cases competitive with photovoltaic parameters of DOA and CDOA.